Time-of-Flight Angiography in Ultra-High-Field 7 T MRI for the Evaluation of Peroneal Perforator Arteries Before Osseomyocutaneous Flap Surgery - Wiesmüller, Marco; Meixner, Christian; Weber, Manuel; Kesting, Marco Rainer; Nagel, Armin M.; Wüst, Wolfgang; May, Matthias; Roemer, Frank W.; Uder, Michael; Heiß, Rafael (Investigative Radiology, 2023)
OBJECTIVES: Presurgical identification and morphologic characterization of the peroneal perforator arteries (PPAs) are essential for osseomyocutaneous flap surgery. The aim of this study was to evaluate PPAs using time-of-flight (TOF) angiography in 7 T magnetic resonance imaging in comparison with dual-energy computed tomographic angiography (CTA). MATERIALS AND METHODS: In this prospective study, TOF angiography and CTA of both lower legs were acquired before flap surgery from 07/2019 to 02/2020. Magnetic resonance imaging was performed using a dedicated 28-channel knee coil with an acquisition time of 9:55 minutes (voxel size: 0.4 × 0.4 × 0.8 mm). Computed tomographic angiography was acquired with a third-generation dual-source computed tomography on the same day. Virtual monoenergetic reconstructions at 40 keV photon energy served as the standard of reference for PPA identification and subtyping. Two independent readers assessed the image quality, quantity, length assessment, and classification according to surgical considerations of PPAs for TOF angiography and CTA. Both TOF angiography and CTA were used for presurgical flap design and were evaluated by an orofacial surgeon. RESULTS: Ten patients (mean age, 59.9 ± 14.9 years; 7 men) were included. Time-of-flight angiography and CTA identified 53 and 51 PPAs in total, respectively. Time-of-flight angiography showed superior image quality (both readers, P < 0.05). Time-of-flight angiography enabled specific classification of PPA subtypes more often (53 vs 39; P < 0.05), and both readers reported higher diagnostic confidence for TOF angiography than CTA in all patients (interrater agreement κ = 0.8; P < 0.05). Regarding length assessment, PPAs were significantly more conspicuous with TOF angiography (TOF mean , 50 ± 11 mm; CTA mean , 40 ± 9 mm; P = 0.001). In comparison with CTA, TOF angiography prospectively changed the orofacial surgeon's final decision on the presurgical selected PPAs in 60% of cases. CONCLUSIONS: Presurgical assessment of PPAs is feasible using TOF in 7 T magnetic resonance imaging. Moreover, TOF angiography was superior to CTA for classifying and identifying PPAs, which may facilitate the planning of reconstructive surgery.
CRIS-Team Scopus Importer:2023-02-24